(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This paper provides a comprehensive overview of the evolving role of paramedics working in tandem with nurses in emergency medical services (EMS). It examines the historical context, changing dynamics in healthcare delivery, collaborative models in practice, training and education requirements, challenges and barriers, and future directions of this critical partnership. Through a synthesis of literature review, case studies, and analysis of current trends, the paper highlights the benefits of interdisciplinary collaboration between paramedics and nurses in enhancing patient outcomes and healthcare system efficiency. Key considerations include training and education, addressing challenges, policy implications, and opportunities for further research.